Case Report on Autoimmune Hemolytic Anemia: A Mask of Malignancy! - Sampagar, Abhilasha; Patil, Neha Giridhar; Bartakke, Sandip; Shrividya, S (Indian Journal of Medical and Paediatric Oncology, 2020)
A 10-year-old boy with autoimmune hemolytic anemia (AIHA) was treated at a local setup with repeated blood transfusions and steroids considering an idiopathic etiology. After 7 months of unresponsiveness, the child started developing recurrent fever with night sweats and pain in the abdomen which was diagnosed as tuberculosis on account of granulomatous necrotizing lesion on computed tomography (CT)-guided lymph node biopsy and treated for the same. Four months later, when the child presented to our center in anemic heart failure, work-up with positron emission tomography-CT and excisional biopsy of mesenteric lymph node led to the diagnosis of advanced Hodgkin's lymphoma with B symptoms. AIHA in pediatric age group, unlike in adults, is usually secondary. Our report stresses on a thorough evaluation of AIHA as it can mask a malignancy for a long duration and alter its course if treated with steroids, making the patient resistant to further chemotherapy.
Keywords: Autoimmune hemolytic anemia; Hodgkin's lymphoma; tuberculosis